Total Flavonoid Content of the Bark Extract of Salacca edulis Reinw - Ardin, Nisradhiyah Caesarika; Pratama, Mamat; Widiastuti, Harti; Fawwaz, Muammar (Universitas Muslim Indonesia, 2022)
Salak fruit (Salacca edulis Reinw) is one of the fruits whose bark is not used but contains chemical components in the form of secondary metabolites that are beneficial to health. A previous study reported that the bark of salak fruit has potential as an anti-diabetic, antioxidant. The bark of Salak fruit is traditionally beneficial for the treatment of diabetes mellitus by drying then boiling and drinking the boiled water. Therefore, this study aims to determine the total flavonoid content of the bark extract of the pondoh and honey varieties of salak fruit. A sample of 30 g was dissolved with ethanol in a 10 mL volumetric flask, then 1 mL was pipette and added with 0.2 ml AlCl3 and 0.2 mL potassium acetate then allowed to stand for 30 min at 25°C. After being allowed to stand, it was measured on a UV-Vis spectrophotometer with a wavelength of 442 nm. In the measurement with UV-Vis spectrophotometer, the total flavonoid content of the salak bark extract of pondoh and honey varieties were 5.18 mg QE/g and 5.77, respectively.